2015
DOI: 10.3109/13697137.2014.995164
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to oral bisphosphonates: 30 more minutes in dosing instructions matter

Abstract: Despite relatively high adherence to the treatment, most patients do not follow dosing instructions. Reduced bioavailability, particularly of monthly ibandronate, can be expected in clinical practice. Adherence-related outcomes are associated with beliefs about the oral treatment with bisphosphonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 29 publications
1
20
1
1
Order By: Relevance
“…Previous research evaluating the translated versions of the BMQ had demonstrated similar values for internal consistency, with the Portuguese version and the Sinhalese version having a Cronbach’s alpha coefficient of 0.66 and 0.65, respectively [ 30 , 31 ]. Although the Cronbach’s alpha value for the Czech translation in our analysis was somewhat lower than in the other Czech study (0.85 for Necessity and 0.82 for Concerns), the high values indicate that both versions are suitable for measurement [ 17 ]. In the Polish version the alpha coefficient for Necessity was between 0.79 and 0.82, while for Concerns it was between 0.65 and 0.70, depending on the group participating in the study [ 20 ].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Previous research evaluating the translated versions of the BMQ had demonstrated similar values for internal consistency, with the Portuguese version and the Sinhalese version having a Cronbach’s alpha coefficient of 0.66 and 0.65, respectively [ 30 , 31 ]. Although the Cronbach’s alpha value for the Czech translation in our analysis was somewhat lower than in the other Czech study (0.85 for Necessity and 0.82 for Concerns), the high values indicate that both versions are suitable for measurement [ 17 ]. In the Polish version the alpha coefficient for Necessity was between 0.79 and 0.82, while for Concerns it was between 0.65 and 0.70, depending on the group participating in the study [ 20 ].…”
Section: Discussionmentioning
confidence: 89%
“…It is worth noting that validated translations already exist for the BMQ-Specific in both the Czech and Polish languages. The Czech version tested general drug use of patients with either diabetes, hypertension or rheumatic disease [ 16 ], and was later used to study the adherence to oral bisphosphonates [ 17 ]. In the Czech validation study, principal component analysis was performed to explore the structure of factors, and reliability was also investigated by Cronbach’s alpha [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With specific reference to osteoporosis, simplification of dosing regimens of bisphosphonates (once-a-week and once-a-month) was found to have only a mild impact on medication adherence, whereas monitoring/supervision showed no impact on medication persistence [10]. However, the methods with a higher probability to improve adherence seem to be those which involve the patients in a higher understanding of risk [12,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous study in patients with HIV found that medication regimens with more complex administration instructions were associated with higher rates of non‐adherence . As shown in patients with osteoporosis, poor adherence to dosing instructions for bisphosphonates is common despite good compliance to the treatment . Non‐adherence to medication administration instructions can affect treatment outcomes and increase risks of drug‐related adverse effects.…”
Section: Discussionmentioning
confidence: 99%